EFFECTIVE STRATEGIES FOR MASTERING A FOREIGN LANGUAGE IN THE DIGITAL AGE (Лучшие интеллектуальные исследования, 2025)
Abstract In the era of rapid globalization, multilingualism has become a fundamental skill across disciplines and professions. This article explores the most effective, research-based strategies for foreign language acquisition in a digital context. The author emphasizes learner autonomy, daily immersion, and the selective use of technology as key components for achieving fluency. Drawing from personal experience and linguistic theory, the article identifies common pitfalls in language instruction and provides practical recommendations for vocabulary retention, grammar acquisition, pronunciation improvement, and spoken communication.